"There's No Sense to It": A Posthumanist Ethnography of Agency in Methamphetamine Recovery. (September 2022) - Brookfield, Samuel; Selvey, Linda; Maher, Lisa; Fitzgerald, Lisa
The orthodox construction of agency within addiction recovery discourse is built upon a fault line between two conflicting principles: that people who use drugs in harmful ways cannot control their behavior, but that they can also regain that control through intentional effort. The conceptual confusion inherent in this framework can harm people using drugs by producing inadequate accounts of commonly invoked aspects of recovery such as "triggers, " "self-control, " and "addictive behavior." This ethnographic study involved qualitative interviews and observations with nine people over 6 months as they engaged in recovery from harmful methamphetamine use, to explore their experiences of agency, and how these experiences could be shaped by the discourse of volition/compulsion. Thematic analysis was conducted using a posthumanist theoretical framework. We found "relapse triggers" to be diffuse aspects of particular environments rather than specific stimuli, able to provoke what would normally be considered conscious, intentional behavior rather than only autonomic or "mindless" processes. Participants also described their identities as internally divided and multiple, with drug related behaviors separated from their true selves. Finally, agency was experienced as emergent and distributed rather than as a particular resource located within individuals. Attending to these complex experiences of agency can help resolve the tension between loss of control and personal responsibility for people who use drugs, by renegotiating the historically imposed categorical distinction between volitional and compelled actions, and the cultural constructions of "addictive" versus "normal" behavior.